2002
DOI: 10.1136/jmg.39.3.e12
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of BRCA2 germline mutations to hereditary breast/ovarian cancer in Germany

Abstract: Breast cancer is the most common malignancy affecting women world wide.1 Approximately 1 in 10 women will develop breast cancer during their life time 2 and 5-10% of all breast cancers, in particular those with an early age of onset, are the result of a genetic predisposition owing to the inheritance of a dominant susceptibility gene(s).In the context of high risk families, one important gene is the BRCA2 gene located on chromosome 13q12-13. BRCA2 was localised to chromosome 13q by linkage analysis in 1994 3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The absence of any index cases harboring such complex rearrangements could be due to selection criteria, as BRCA1 mutations are more frequently observed in HBOC than HBC families [12][13][14]. Although a recent review of 54 French Canadian HBOC families from our group did not include an analysis of large deletions [10], a further investigation by MLPA analysis of the 9 mutation-negative HBOC families with serous histopathological subtype ovarian cancers did not reveal any evidence for missed BRCA1/2 mutations (unpublished results).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The absence of any index cases harboring such complex rearrangements could be due to selection criteria, as BRCA1 mutations are more frequently observed in HBOC than HBC families [12][13][14]. Although a recent review of 54 French Canadian HBOC families from our group did not include an analysis of large deletions [10], a further investigation by MLPA analysis of the 9 mutation-negative HBOC families with serous histopathological subtype ovarian cancers did not reveal any evidence for missed BRCA1/2 mutations (unpublished results).…”
Section: Discussionmentioning
confidence: 98%
“…The frequency of mutation-positive HBOC families increased with the number of ovarian cancer cases, particularly if they had a serous histopathological subtype of ovarian cancer [10,11]. Independent studies of French Canadian cancer families [12] as well as of other populations of European descent [11,13,14], also reported a higher proportion of mutationpositive HBOC families than HBC families. These findings support the notion that the majority of HBOC families are accounted for by BRCA1 and BRCA2 mutations and have rationalized the exclusion of cancer families with ovarian cancer cases in studies aimed at finding additional alleles that confer a high risk for breast cancer [15][16][17].…”
Section: Introductionmentioning
confidence: 87%
“…SSCP and PTT analysis was performed as previously described [16,17]. DHPLC analysis was performed using the WAVE system (Transgenomics, Omaha, NE, USA).…”
Section: Mutation Screeningmentioning
confidence: 99%
“…However, none of the four male breast cancer patients included in our study showed BRCA2 mutation (except an intronic alteration in family MBF88, Table 3). Few other investigators also failed to demonstrate such association (Hamann et al 2002). It is presumed that some other genes (other than BRCA2) may be involved in the pathogenesis of male breast cancer in these families.…”
Section: Discussionmentioning
confidence: 93%